THE CARL ROGERS’S PSYCHOLOGY AND PAULO FREIRE’S PEDAGOGY: REFLECTIONS ABOUT TEACHING - Rios de Freitas, Patrícia; Tinoco Boechat, Ieda (LINKSCIENCEPLACE, 2026)
The project thematizes the contributions of Roger‟s humanism and Paulo Freire‟s pedagogy in teaching practice. Has, in that way, as its general objective analyse the correlation of Carl Rogers‟s human being conception in its person-centered approach with Paulo Freire‟s studies and understanding about education of freedom. Therefore, is told about Carl Roger‟s person-centered therapy and his student-centered approach; it‟s addressed about Freire‟s theory highlighting the difference between banking education and liberating education; and it is explained about the correlates in the change of politics in professions of help, proposed by Rogers, with Paulo Freire‟s pedagogy of autonomy. The methodology used, in its qualitative character, is the bibliographic research based on Rogers (2001), Freire (1987, 2013) and Zimring (2010). The research shows that are expressive convergences in Carl Rogers‟s and Paulo Freire‟s thought, about the educational scope. It is concluded that the pedagogical practice that are based on Freire‟s pedagogy and Rogers‟s student-centered approach can be effective, not just for the student‟s critical development, as well as enrich the studenteducator relationship.